Respuesta :
Answer:
(3,6)
Step-by-step explanation:
y = 2x
x+y = 9
; x+(2x) = 9
3x = 9
x = 3
y = 2x
y = 2(3)
y = 6
Hello there here is the problem you gave us
[tex]y=2x,x+y=9[/tex]
You want to us to solve this by substitution,
_______________________
- [tex]y=2x[/tex]
- [tex]x= \frac{1}{2}y[/tex]
_______________________
we can substitute [tex]y[/tex] for [tex]2x[/tex] and get the equation
[tex]x+2x=9[/tex], do the simple algebra and we get that [tex]x=3[/tex], remember though [tex]y=2x[/tex], plug in the value that [tex]x=3[/tex] and get that [tex]y=6[/tex]
_______________________
[tex]{\huge{\boxed{\mathfrak{Answer}}}[/tex]
- [tex]x=3[/tex]
- [tex]y=6[/tex]